Effects of postoperative adjuvant steroid therapy on the outcomes of biliary atresia: A systematic review and updated meta-analysis - Yang, Chang-zhen; Zhou, Yan; Ke, Meng; Gao, Ru-yue; Ye, Shi-ru; Diao, Mei; Li, Long (Frontiers in Pharmacology, 2022)
Background: Postoperative adjuvant steroid therapy is regarded as the conventional treatment for patients with biliary atresia (BA) who have undergone Kasai portoenterostomy (KP). However, whether the steroid therapy can improve BA outcomes is controversial. This meta-analysis aimed to evaluate the effects of adjuvant steroid therapy on the surgical prognosis of BA. Methods: We searched related studies published in PubMed, Embase, Web of Science, Cochrane, and the Chinese National Knowledge Infrastructure database up to May 2022. Data on the effect of steroid use on the clinical prognosis of the patients, including the jaundice clearance rate (JCR), native liver survival rate (NLSR) at 6, 12, and 24 months after KP, and the incidence of cholangitis, were extracted. Subgroup analyses based on age at KP, administration method, initial dosage, and steroid type were conducted. Statistical analysis was conducted using Stata/SE 12.0. Results: Eleven articles (a total of 1032 patients) were included in the present meta-analysis. The results demonstrated that postoperative adjuvant steroid therapy improved JCR at the 6/12/24-month follow-up (RR: 1.37, 95% CI: 1.20–1.56, p<0.00001; RR:1.50, 95% CI, 1.13–2.00, p=0.005; RR: 1.41, 95% CI: 1.14–1.75, p=0.002) and improved NLSR at the 12/24-month follow-up (RR: 1.29, 95% CI: 1.10–1.51, p=0.002; RR: 1.33, 95% CI: 1.13–1.57, p=0.001). Postoperative adjuvant steroid therapy also decreased the incidence of postoperative cholangitis (RR: 0.76, 95% CI: 0.58–0.99, p=0.043). However, steroids did not significantly improve NLSR at the 6-month follow-up (RR: 1.05; 95% CI: 0.97–1.14; p=0.240). Furthermore, subgroup analyses confirmed that four variables (age at KP, administration method, initial dosage, and steroid type) could affect the efficacy of steroids in BA patients. Conclusion: Postoperative adjuvant steroid therapy can significantly improve clinical outcomes, except for NSLR at the 6-month follow-up. The superiority of steroid therapy was more remarkable in patients aged ≤70 days at KP than in those aged >70 days. Additionally, compared with other steroid regimens, intravenous followed by oral steroid administration method, medium initial dosage, and administering methylprednisolone or methylprednisolone followed by prednisone seemed to have the more reliable efficiency on clinical outcomes. Further studies with more rational steroid regimens are warranted.